Modified sodium sulfate material and preparation method thereof, sodium ferric sulfate positive electrode material, positive electrode plate, sodium ion battery and electric equipment

By doping nitrogen-doped carbon to coat sodium sulfate material, the problem of sodium ferric sulfate being sensitive to air humidity and oxidation atmosphere is solved, its conductivity and water absorption resistance are improved, and the circulation stability and battery performance of sodium ion batteries are enhanced.

CN120300154APending Publication Date: 2025-07-11NINGBO RONBAY LITHIUM BATTERY MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510403023.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-31
Publication Date
2025-07-11

AI Technical Summary

Technical Problem

Sodium ferric sulfate is extremely sensitive to humidity and oxidation atmosphere in the air, and is prone to absorb water and deterioration, resulting in deterioration of specific capacity and circulation performance, affecting its stability and life in sodium ion batteries.

Method used

The sodium sulfate material coated with nitrogen-doped carbon is used to prevent sodium sulfate from contacting air through the N-doped C shell, reduce water absorption, and induce defects in the C microstructure, enhance conductivity, and form conductive channels of polyprism particles to ensure that each element fully reacts during the preparation of sodium ferric sulfate.

Benefits of technology

The conductivity and water absorption resistance of the positive electrode material of sodium ferric sulfate are improved, the circulation stability and battery performance of sodium ion batteries are enhanced, and the problem of sodium ferric sulfate is easy to absorb water in the air.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120300154A_ABST
    Figure CN120300154A_ABST
Patent Text Reader

Abstract

The invention particularly relates to a modified sodium sulfate material and a preparation method thereof, a sodium ferric sulfate positive electrode material, a positive electrode plate, a sodium ion battery and electric equipment. The modified sodium sulfate material provided by the invention comprises a shell and polygon prism particles located in the shell, and the material does not easily absorb water and is beneficial to full reaction of all elements in the subsequent sodium ferric sulfate preparation process. The sodium ferric sulfate material provided by the invention has relatively low water absorption and relatively good conductivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cathode materials for sodium-ion batteries, and particularly to a modified sodium sulfate material and its preparation method, a sodium iron sulfate cathode material, a cathode electrode sheet, a sodium-ion battery, and an electrical device. Background Art

[0002] In recent years, with the continuous exacerbation of global environmental problems, the development of new renewable energy has become extremely urgent. Given the abundance of sodium resources, low manufacturing costs, and excellent performance, sodium-ion batteries have great potential to become the mainstream energy storage devices in the future development of the new energy industry.

[0003] The cathode material is a crucial part of the battery system, and its properties such as cycle stability, output voltage, thermal stability, output capacity, and power density have a decisive impact on the performance of the entire battery. The performance of sodium-ion batteries is largely limited by the choice of their cathode materials. Polyanion-type cathode materials have attracted much attention due to their high working voltage, stable lattice structure, and excellent sodium-ion storage kinetics. Among them, sodium iron sulfate, as a polyanion-type material, not only has these advantages but also has additional advantages such as low cost, simple preparation process, environmental friendliness, and low production energy consumption. Therefore, it is regarded as one of the most promising cathode materials for promoting the industrialization of sodium-ion batteries. However, despite the many advantages of sodium iron sulfate, its disadvantages cannot be ignored. Sodium iron sulfate is extremely sensitive to humidity and oxidative atmosphere in the air, easily absorbs water and deteriorates, and is extremely easy to be oxidized to Fe 3+ , thereby deteriorating its specific capacity and cycle performance, which not only increases the difficulty of pulping and coating but also limits the stability and lifespan of sodium iron sulfate in practical applications.

[0004] Therefore, it is of great significance to study sodium iron sulfate to reduce its water absorption while taking into account its conductivity. Summary of the Invention

[0005] The present invention provides a modified sodium sulfate material, which is not easy to absorb water and is conducive to the full reaction of each element in the subsequent preparation process of sodium iron sulfate. The prepared sodium iron sulfate cathode material has better conductivity and lower water absorption.

[0006] The sodium iron sulfate cathode material provided by the present invention has both better conductivity and lower water absorption.

[0007] In the first aspect of the present invention, a modified sodium sulfate material is provided, which includes a shell and prismatic particles located inside the shell. The composition of the shell includes N and C, and the composition of the prismatic particles includes C and sodium sulfate.

[0008] The above-mentioned modified sodium sulfate material is a nitrogen-doped carbon-coated sodium sulfate material. On the one hand, the N-doped C shell can prevent sodium sulfate from contacting with air, thereby reducing its water absorption in air. On the other hand, the N-doped C shell can effectively induce a large number of defects in the C microstructure. The increase in defect sites can enhance the conductivity of C. The conductive channels formed by the prismatic particles are beneficial to the rapid diffusion of ions, enabling the full reaction of various elements during the subsequent preparation of sodium iron sulfate, thereby improving its phase purity and crystallinity, enhancing its ionic conductivity, and improving the cycle stability of the prepared battery. This special structure also solves the problems of small reaction area of solid spheres and low loose packing of hollow spheres that are difficult to scale up, and can ensure sufficient contact area with other raw materials in the subsequent process, making the reaction more complete.

[0009] For the modified sodium sulfate material described above, the prismatic particles are aggregated by rod-shaped particles.

[0010] For the modified sodium sulfate material described above, the moisture content of the modified sodium sulfate material ≤ 1000 ppm.

[0011] For the modified sodium sulfate material described above, the diameter of the rod-shaped particles is 200 - 600 nm, and the length is 7 - 12 μm.

[0012] For the modified sodium sulfate material described above, the diameter of the shell is 15 - 25 μm.

[0013] The present invention also provides a preparation method of a modified sodium sulfate material, which at least includes the steps of preparing a precursor by spray drying a precursor material containing a carbon source, a nitrogen source, and sodium sulfate, and sintering the precursor under a protective atmosphere to obtain the modified sodium sulfate;

[0014] Among them, the viscosity of the nitrogen source is higher than that of the carbon source, and the carbon source is an organic carbon source. The K value of the nitrogen source ≥ 23, and the dosage of the nitrogen source is 5 - 10 wt% of the carbon source.

[0015] In the preparation of the modified sodium sulfate material provided by the present invention, the viscosity of the nitrogen source is higher than that of the carbon source. The carbon source combines with sodium sulfate to form a complex with a lower viscosity, while the nitrogen source has a higher viscosity. Therefore, its interaction with metal ions is relatively indirect. During the particle preparation process, the complex with a lower viscosity presents primary rod-shaped particles, which tend to aggregate to form secondary prismatic particles, while the nitrogen source with a higher viscosity tends to diffuse outward into a sphere, thereby forming a morphology of a nitrogen-doped carbon shell coating the prismatic particles. This method is simple to operate and easy to implement.

[0016] For the preparation method described above, the inlet temperature of spray drying is 160 - 210 °C, the outlet temperature is 60 - 100 °C, the sintering temperature of the precursor is 500 - 800 °C, and the sintering time is 6 - 12 h.

[0017] According to the preparation method described above, the carbon source is one or more of citric acid, glucose, folic acid, fructose, lactose, sucrose, maltose, and starch, and the nitrogen source is PVP.

[0018] The present invention also provides a sodium iron sulfate cathode material, and the structural general formula of the sodium iron sulfate cathode material is Na 2.5 Fe 1.75-x A x (SO4)3@CN, where 0 < x ≤ 0.05 and the A ion is a hydrophobic metal ion.

[0019] For the sodium iron sulfate cathode material described above, after doping metal ions into the sodium iron sulfate cathode material, the diffraction peak of the crystal plane at 15.45° in its X-ray diffraction pattern shifts to the left, and the shifting amplitude is 0 - 0.2°.

[0020] For the sodium iron sulfate cathode material described above, the A ion and Fe 2+ have different ionic radii.

[0021] For the sodium iron sulfate cathode material described above, the A ion is one or more of Mg 2+ , Ni 2+ , Cu 2+ , Zn 2+ .

[0022] For the sodium iron sulfate cathode material described above, it is prepared from a mixed material including the above-mentioned modified sodium sulfate material, an iron source, and a doping metal with a mass ratio of ≥0.

[0023] For the sodium iron sulfate cathode material described above, the mixed material is sintered under a protective atmosphere to obtain the sodium iron sulfate cathode material. The sintering temperature of the mixed material is 320 - 400 °C, and the sintering time is 8 - 24 h.

[0024] For the sodium iron sulfate cathode material described above, the mixed material is ball-milled and then sintered; among them, the ball-milling speed is 200 - 500 r, and the time is 1 - 5 h.

[0025] For the sodium iron sulfate cathode material described above, the mixed material further includes a reducing agent, and the reducing agent is selected from one or more of ascorbic acid, oxalic acid, citric acid, pyrrole, tea polyphenols, or sodium sulfite.

[0026] The present invention also provides a cathode material including the above-mentioned sodium iron sulfate cathode material.

[0027] The present invention also provides a cathode plate including the above-mentioned cathode material.

[0028] The present invention also provides a sodium-ion battery including the above-mentioned cathode plate.

[0029] The present invention also provides an electronic device, including the above-mentioned sodium-ion battery. Description of the Drawings

[0030] Figure 1 XRD pattern of the modified sodium sulfate prepared in Example 1;

[0031] Figure 2 SEM images of the modified sodium sulfate prepared in Example 1, where A and B are SEM images at different magnifications respectively;

[0032] Figure 3 Energy spectrum diagrams of C and N elements of the sodium sulfate material prepared in Example 1;

[0033] Figure 4 SEM image of the modified sodium sulfate prepared in Comparative Example 2;

[0034] Figure 5 Charge-discharge curves of Example 1 and Comparative Example 2 at 0.1C;

[0035] Figure 6 5C cycle curves of Example 1, Comparative Example 1 and Comparative Example 2;

[0036] Figure 7 XRD patterns of the positive electrode materials prepared in Example 3 and Comparative Example 4. Detailed Embodiments

[0037] To make the objectives, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are some but not all of the embodiments of the present invention. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the protection scope of the present invention.

[0038] Based on the problems that the existing sodium iron sulfate positive electrode material is sensitive to humidity and oxidation atmosphere in the air, is easy to absorb water and has poor conductivity, the present invention modifies the raw material sodium sulfate for preparing the sodium iron sulfate positive electrode material to obtain a new sodium sulfate material, which is not easy to absorb water and is beneficial to the full reaction of each element in the subsequent preparation process of sodium iron sulfate. The prepared sodium iron sulfate positive electrode material has better conductivity and lower water absorption.

[0039] The modified sodium sulfate material provided by the present invention is a nitrogen-doped carbon-coated sodium sulfate material, which includes a shell and prismatic particles located inside the shell. Among them, the composition of the shell includes N and C, and the composition of the prismatic particles includes C, sodium iron sulfate or sodium iron sulfate with doped metal.

[0040] The modified sodium sulfate material provided by the present invention uses an N-doped C shell. On the one hand, it can prevent sodium sulfate from contacting with air, thereby reducing its water absorption in the air. On the other hand, the N-doped C shell can effectively induce a large number of defects in the C microstructure. The increase in defect sites can enhance the conductivity of C. The conductive channels formed by the multi-prismatic particles are conducive to the rapid diffusion of ions, enabling the full reaction of each element during the subsequent sintering process of sodium iron sulfate, which is beneficial to improving the phase purity and crystallinity, and further enhancing its ionic conductivity and the cycle stability of the prepared battery. This special structure also solves the problems of small reaction area of solid spheres and low loose packing of hollow spheres that are difficult to scale up, and can ensure sufficient contact area with other raw materials in the follow-up, making the reaction more complete.

[0041] In some specific embodiments of the present invention, the multi-prismatic particles are aggregated by rod-shaped particles. Specifically, the rod-shaped particles are particles with a long strip or rod shape, and their length is much greater than the diameter. A plurality of rod-shaped particles are aggregated along the length direction to form multi-prismatic particles. The rod-shaped particles form a conductive channel inside the shell. This unique structure and the interconnected rod-shaped channels ensure the rapid diffusion of ions.

[0042] In some specific embodiments of the present invention, the moisture content of the modified sodium sulfate material is ≤1000 ppm. The lower moisture content is not easy to agglomerate, and can ensure the uniformity of ball milling during the subsequent preparation of sodium iron sulfate, thereby improving the conductivity of the prepared sodium iron sulfate; the lower moisture content can also ensure that no water-absorbing impurity phases are easily formed during the preparation of sodium iron sulfate, thus ensuring that the prepared sodium iron sulfate material is not easy to absorb water.

[0043] In some specific embodiments of the present invention, the diameter of the rod-shaped particles is 200 - 600 nm, such as 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, and the range between any two of the above values, and the length is 7 - 12 μm, such as 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, and the range between any two of the above values. The diameter of the shell is 15 - 25 μm, such as 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm, 21 μm, 22 μm, 23 μm, 24 μm, 25 μm, and the range between any two of the above values.

[0044] During preparation, the multi-prismatic particles may either grow on the inner wall of the shell or break away from the shell. In some specific embodiments of the present invention, the multi-prismatic particles grow on the inner wall of the shell. Specifically, the multi-prismatic particles grow on the inner wall of the shell and gather towards the center of the shell, thus forming a coating structure in which the shell coats the multi-prismatic particles.

[0045] The present invention also provides a method for preparing the above-mentioned modified sodium sulfate material, which at least includes the steps of preparing a precursor by spray drying a precursor material containing a carbon source, a nitrogen source and sodium sulfate, and sintering the precursor under a protective atmosphere; wherein, the viscosity of the nitrogen source is higher than that of the carbon source, the carbon source is an organic carbon source, the K value of the nitrogen source ≥ 23, and the amount of the nitrogen source is 5-10 wt% of the carbon source.

[0046] In the preparation of the modified sodium sulfate material provided by the present invention, it is ensured that the viscosity of the nitrogen source is higher than that of the carbon source. The carbon source combines with sodium sulfate to form a complex with a lower viscosity, while the nitrogen source has a higher viscosity. Therefore, its interaction with metal ions is relatively indirect. During the particle preparation process, the complex with a lower viscosity presents primary rod-shaped particles, which tend to aggregate to form secondary multi-prismatic particles, while the nitrogen source with a higher viscosity tends to diffuse outward into spheres, thus forming a morphology in which a nitrogen-doped carbon shell coats the multi-prismatic particles.

[0047] In the above, the viscosity is also characterized by the K value. The K value of the nitrogen source needs to be ensured to be ≥ 23. Usually, a nitrogen source with a K value of 23-60 is selected because too high a viscosity will affect the material mixing effect and cause blockage during spray drying. Taking polyvinylpyrrolidone (PVP) as an example, exemplarily, raw materials with K values of 23, 27, 30, 40, 50, 60 and any two values between the above can be selected.

[0048] There is no special limitation on the type of carbon source. An inorganic carbon source or an organic carbon source can be selected. In actual preparation, an organic carbon source is usually selected as long as its viscosity is lower than that of the nitrogen source.

[0049] The K value mentioned above refers to the consistency coefficient, which is detected at 25 °C. Taking polyvinylpyrrolidone (PVP) as an example, the average molecular weight corresponding to a K value of 30-60 is 24,000-220,000 Da.

[0050] In the above preparation method, as long as the amount of the nitrogen source is 5-10 wt% of the carbon source, such as 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt% and the range between any two of the above values, products with corresponding morphologies can be obtained. The amount of the carbon source can be adjusted according to the doping amount. Usually, its mass is controlled to be 1-40% of the mass of sodium sulfate, preferably 5-40%. Considering the capacity of the final obtained cathode material, etc., it is usually controlled at 5-20%.

[0051] During spray drying, to avoid excessive moisture in the discharged material due to too low temperature affecting the subsequent process or excessive loss to the equipment caused by too high temperature, the inlet temperature is usually controlled at 160 - 210 °C, such as 160 °C, 170 °C, 180 °C, 190 °C, 200 °C, 210 °C, and the range between any two of the above values, and the outlet temperature is 60 - 100 °C, such as 60 °C, 70 °C, 80 °C, 90 °C, 100 °C, and the range between any two of the above values. Other parameters of spray drying can adopt conventional parameters, for example, the feed rate is 1000 - 3000 ml / h, and the atomizer frequency is 200 - 400 Hz.

[0052] During the sintering of the precursor, it is only necessary to ensure that the organic carbon in the precursor is fully decomposed to form conductive carbon. Exemplarily, the sintering temperature of the precursor particles is 500 - 800 °C, such as 500 °C, 550 °C, 600 °C, 650 °C, 700 °C, 750 °C, 800 °C, and the range between any two of the above values. The sintering time is 6 - 12 h, such as 6 h, 7 h, 8 h, 9 h, 10 h, 11 h, 12 h, and the range between any two of the above values. Among them, preferably, the sintering temperature is 550 - 750 °C, and the sintering time is 8 - 10 h.

[0053] Exemplarily, in the present invention, the carbon source is one or several of citric acid, glucose, folic acid, fructose, lactose, sucrose, maltose, and starch. Further, to ensure that the nitrogen source can be decomposed simultaneously within the temperature range where organic carbon is converted into conductive carbon, the nitrogen source can be selected as PVP (polyvinylpyrrolidone).

[0054] The present invention also provides a sodium iron sulfate cathode material, and the structural general formula of the cathode material is Na 2.5 Fe 1.75-x A x (SO4)3@CN, where 0 < x ≤ 0.05, and the A ion is a hydrophobic metal ion. This material has both better conductivity and lower water absorption.

[0055] The doping of hydrophobic metal ions can not only further reduce the water absorption of the material, but also expand the ion transport channels, reduce the ion diffusion barrier, improve the rate performance, and the mixing entropy effect generated by the doping of multiple metal ions can also stabilize the crystal structure and improve the cycling performance.

[0056] Further, after doping metal ions into the sodium iron sulfate cathode material, the diffraction peak of the crystal plane at 15.45° in its X-ray diffraction (i.e., XRD) pattern shifts to the left, and the shifting amplitude is 0 - 0.2°. This indicates that the metal ions are successfully doped into the lattice, and the lattice parameters are changed, broadening the Na + diffusion channels.

[0057] Furthermore, the sodium iron sulfate cathode material provided by the present invention has a moisture content of ≤900 ppm. Further, when it is exposed to air with a humidity of 70% at 25°C for one week, its structure is stable and no impurity phase appears in the XRD.

[0058] In some other specific embodiments of the present invention, the ionic radius of A ions is different from that of Fe 2+ . By using A ions with an ionic radius different from that of Fe 2+ , when A ions occupy the iron sites, the lattice parameters of the material can be effectively changed, the sodium ion transport channels can be enlarged, the sodium ion transport efficiency can be improved, the charge transfer resistance is reduced, and the electrochemical performance, especially the intrinsic conductivity and rate performance, can be greatly improved. In addition, the mixing entropy effect generated by the doping of multiple metal ions makes the inside of the crystal in a state with a lower free energy, which can enhance the structural stability and improve the cycle performance. Exemplarily, the A ions are one or more of Mg 2+ , Ni 2+ , Cu 2+ , Zn 2+ .

[0059] In some specific embodiments of the present invention, the above-mentioned sodium iron sulfate cathode material is prepared from a mixed material including the above-mentioned modified sodium sulfate material, an iron source, and a doped metal with a mass ratio of ≥0.

[0060] The method for preparing the sodium iron sulfate cathode material from the mixed material can adopt the conventional sintering method in the art. Exemplarily, the sintering temperature of the mixed material is 320 - 400°C, such as 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, and the range between any two of the above values, and the sintering time is 8 - 24 h, such as 8 h, 10 h, 12 h, 14 h, 16 h, 18 h, 20 h, 22 h, 24 h, and the range between any two of the above values. Among them, the preferred sintering temperature is 340 - 380°C, and the sintering time is 10 - 20 h.

[0061] In order to ensure that the iron source can be mixed evenly with the sodium sulfate particles, the mixed material in step 2 is subjected to grinding treatment before sintering. Exemplarily, the mixed material is treated by ball milling, the rotation speed of the ball milling is 200 - 500 r, such as 200 r, 300 r, 400 r, 500 r, and the range between any two of the above values, and the time is 1 - 5 h, such as 1 h, 2 h, 3 h, 4 h, 5 h, and the range between any two of the above values.

[0062] In order to ensure a stable reaction of ferrous ions, a reducing agent is usually added to the mixture in step 2. Exemplarily, the reducing agent is one or several of ascorbic acid, oxalic acid, citric acid, pyrrole, tea polyphenols, or sodium sulfite.

[0063] The present invention also provides a cathode material, including the above-mentioned C / N composite-doped and modified sodium iron sulfate cathode material or the C / N composite-doped and modified sodium iron sulfate cathode material prepared by the above method.

[0064] The present invention also provides a cathode electrode sheet, including the above-mentioned cathode material.

[0065] The present invention also provides a sodium-ion battery, including the above-mentioned cathode electrode sheet.

[0066] The present invention also provides an electronic device, including the above-mentioned sodium-ion battery. Exemplarily, the electronic device is an electric bicycle, an electric vehicle, a battery, a smart phone, a tablet computer, a laptop computer, a drone, etc.

[0067] The following describes in detail the C / N composite-doped and modified sodium iron sulfate cathode material of the present invention, its preparation method and application with reference to specific embodiments.

[0068] The polyvinylpyrrolidone (PVP) in the following examples and comparative examples is a Macklin reagent.

[0069] In the following examples, the composition of the modified sodium sulfate material shell and the prismatic particles is determined by energy dispersive spectroscopy; the diameter, length of the prismatic particles and the diameter of the shell are all obtained by scanning electron microscopy (SEM).

[0070] Example 1

[0071] This example provides a modified sodium sulfate, sodium iron sulfate cathode material and its preparation method.

[0072] (1) Preparation of modified sodium sulfate material NaSO4@C / N

[0073] 893.3 g of sodium sulfate, 106.7 g of citric acid, and 10.67 g of PVP (K value is 30) are dissolved in 10 L of pure water. After stirring evenly, the precursor is obtained by spray drying. When spray drying, the inlet temperature is 180 °C, the outlet temperature is 80 °C, the feeding rate is 2000 ml / h, and the atomizer frequency is 300 Hz. The precursor is sintered at 650 °C for 10 h in a nitrogen atmosphere to obtain nitrogen-doped carbon-coated sodium sulfate, namely NaSO4@C / N.

[0074] After detection and analysis, it has a structure including a shell and prismatic particles located inside the shell. The average diameter of the rod-shaped particles inside the shell is about 350 nm, the average length is about 10 μm, and the diameter of the shell is about 17 μm. Among them, Figure 1 is its XRD pattern, Figure 2 is its SEM images at different magnifications, Figure 3It is the energy spectrum diagram of C and N elements.

[0075] (2) Sodium iron sulfate Na 2.5 Fe 1.73 Cu 0.01 Zn 0.01 (Preparation of Na

[0076] According to the molar ratio of Na 2.5 Fe 1.73 Cu 0.01 Zn 0.01 (SO4)3@C / N, take 40.04 g of NaSO4@C / N, 60.17 g of FeSO4, 0.37 g of ZnSO4, 0.37 g of CuSO4, and 2.98 g of ascorbic acid. After ball milling and mixing, sinter at 350 °C in nitrogen for 16 h, and then pulverize to obtain Na 2.5 Fe 1.73 Cu 0.01 Zn 0.01 (SO4)3@C / N. After testing, it is found that the carbon content in Na 2.5 Fe 1.73 Cu 0.01 Zn 0.01 (SO4)3@C / N is about 3.6%.

[0077] Example 2

[0078] This example provides a modified sodium sulfate and sodium iron sulfate cathode material and its preparation method.

[0079] (1) Preparation of modified sodium sulfate material NaSO4@C / N

[0080] Dissolve 946.6 g of sodium sulfate, 53.4 g of citric acid, and 5.34 g of PVP (K value is 30) in 10 L of pure water. After stirring evenly, obtain the precursor through spray drying. When spray drying, the inlet temperature is 200 °C, the outlet temperature is 80 °C, the feeding rate is 2000 ml / h, and the atomizer frequency is 300 Hz. Sinter the precursor in a nitrogen atmosphere at 700 °C for 8 h to obtain sodium sulfate coated with nitrogen-doped carbon, that is, NaSO4@C / N.

[0081] (2) Sodium iron sulfate Na 2.5 Fe 1.7 Zn 0.02 Cu 0.03 (SO4)3@C / N preparation

[0082] According to Na 2.5 Fe 1.7 Zn 0.02 Cu 0.03(SO4)3 was prepared by taking 40.01 g of NaSO4@C / N, 58.20 g of FeSO4, 0.74 g of ZnSO4, 1.1 g of CuSO4, and 2.96 g of ascorbic acid, ball-milling and mixing them, sintering at 380 °C in nitrogen for 14 h, and pulverizing to obtain Na 2.5 Fe 1.7 Zn 0.02 Cu 0.03 (SO4)3@C / N. After testing, it was found that Na 2.5 Fe 1.7 Zn 0.02 Cu 0.03 (SO4)3@C / N had a carbon content of approximately 2.3%.

[0083] Example 3

[0084] This example provides a modified sodium sulfate, sodium iron sulfate cathode material and its preparation method.

[0085] (1) Preparation of the modified sodium sulfate material NaSO4@C / N

[0086] 900 g of sodium sulfate, 100 g of glucose, and 10 g of PVP (K value of 30) were fully dissolved in 10 L of pure water. After stirring evenly, the precursor was obtained by spray drying. When spray drying, the inlet temperature was 160 °C, the outlet temperature was 80 °C, the feed rate was 2000 ml / h, and the atomizer frequency was 300 Hz. The precursor was sintered at 550 °C in a nitrogen atmosphere for 10 h to obtain nitrogen-doped carbon-coated sodium sulfate, namely NaSO4@C / N.

[0087] (2) Preparation of sodium iron sulfate Na 2.5 Fe 1.73 Cu 0.01 Mg 0.01 (SO4)3@C / N

[0088] According to the molar ratio of Na 2.5 Fe 1.73 Cu 0.01 Mg 0.01 (SO4)3, 40.51 g of NaSO4@C / N, 57.66 g of FeSO4, 0.37 g of CuSO4, 0.28 g of MgSO4, and 2.88 g of ascorbic acid were taken, ball-milled and mixed, sintered at 400 °C in nitrogen for 10 h, and pulverized to obtain Na 2.5 Fe 1.73 Cu 0.01 Mg 0.01 (SO4)3@C / N. After testing, it was found that Na 2.5 Fe 1.73 Cu 0.01 Mg 0.01The carbon content in (SO4)3@C / N is approximately 3.56%. Figure 7 This is the XRD pattern of the cathode materials prepared in this example and Comparative Example 4. It can be seen from Figure 7 that after doping with metal ions, the diffraction peak of the crystal plane at 15.45° in the X-ray diffraction pattern shifts to the left, and the shifting amplitude is 0 - 0.2°.

[0089] Example 4:

[0090] This example provides a modified sodium sulfate and sodium iron sulfate cathode material and its preparation method.

[0091] (1) Preparation of the modified sodium sulfate material NaSO4@C / N

[0092] Dissolve 786.4 g of sodium sulfate, 213.6 g of citric acid, and 21.36 g of PVP (K value is 40) in 10 L of pure water. After stirring evenly, obtain the precursor through spray drying. When spray drying, the inlet temperature is 210 °C, the outlet temperature is 100 °C, the feeding rate is 2000 ml / h, and the atomizer frequency is 300 Hz. Sinter the precursor in a nitrogen atmosphere at 750 °C for 8 h to obtain nitrogen-doped carbon-coated sodium sulfate, that is, NaSO4@C / N.

[0093] (2) Preparation of sodium iron sulfate Na 2.5 Fe 1.72 Cu 0.01 Ni 0.01 Zn 0.01 (SO4)3@C / N

[0094] According to the molar ratio of Na 2.5 Fe 1.72 Cu 0.01 Ni 0.01 Zn 0.01 Take 40.04 g of NaSO4@C / N, 59.60 g of FeSO4, 0.35 g of NiSO4, 0.37 g of ZnSO4, 0.37 g of CuSO4, and 2.98 g of ascorbic acid according to the molar ratio of (SO4)3. After ball milling and mixing, sinter in nitrogen at 380 °C for 12 h, and then crush to obtain Na 2.5 Fe 1.72 Cu 0.01 Ni 0.01 Zn 0.01 (SO4)3@C / N. After testing, it is found that the carbon content in Na 2.5 Fe 1.72 Cu 0.01 Ni 0.01 Zn 0.01 (SO4)3@C / N is approximately 6.8%.

[0095] Example 5:

[0096] This embodiment provides a modified sodium sulfate, sodium iron sulfate cathode material and a preparation method thereof.

[0097] (1) Preparation of modified sodium sulfate material NaSO4@C / N

[0098] Dissolve 786.4 g of sodium sulfate, 213.6 g of folic acid, and 11.8 g of PVP (K value is 60) in 10 L of pure water. After stirring evenly, obtain a precursor through spray drying. When spray drying, the inlet temperature is 180 °C, the outlet temperature is 80 °C, the feeding rate is 2000 ml / h, and the atomizer frequency is 300 Hz. Sinter the precursor in a nitrogen atmosphere at 700 °C for 10 h to obtain nitrogen-doped carbon-coated sodium sulfate, that is, NaSO4@C / N.

[0099] (2) Preparation of sodium iron sulfate Na 2.5 Fe 1.7 Ni 0.02 Mg 0.02 Zn 0.01 (SO4)3@C / N

[0100] According to the molar ratio of Na 2.5 Fe 1.7 Ni 0.02 Mg 0.02 Zn 0.01 (SO4)3, take 40.03 g of NaSO4@C / N, 59.25 g of FeSO4, 0.71 g of NiSO4, 0.55 g of MgSO4, 0.37 g of ZnSO4, and 2.96 g of ascorbic acid. After ball milling and mixing, sinter in nitrogen at 320 °C for 24 h, and then pulverize to obtain Na 2.5 Fe 1.7 Ni 0.02 Mg 0.02 Zn 0.01 (SO4)3. After testing, it is found that the carbon content in Na 2.5 Fe 1.7 Ni 0.02 Mg 0.02 Zn 0.01 (SO4)3@C / N is about 2.4%.

[0101] Comparative Example 1:

[0102] This comparative example provides a modified sodium sulfate, sodium iron sulfate cathode material and a preparation method thereof.

[0103] (1) Preparation of modified sodium sulfate material NaSO4@C

[0104] Dissolve 893.3 g of sodium sulfate and 106.7 g of citric acid in 10 L of pure water. After stirring evenly, obtain the precursor through spray drying. When spray drying, the inlet temperature is 180 °C, the outlet temperature is 80 °C, the feeding rate is 2000 ml / h, and the atomizer frequency is 300 Hz. Sinter the precursor in a nitrogen atmosphere at 650 °C for 10 h to obtain carbon-coated sodium sulfate, namely NaSO4@C.

[0105] (2) Preparation of sodium iron sulfate Na 2.5 Fe 1.73 Cu 0.01 Zn 0.01 (SO4)3@C

[0106] According to the molar ratio of Na 2.5 Fe 1.73 Cu 0.01 Zn 0.01 (SO4)3, take 40.04 g of NaSO4@C, 60.17 g of FeSO4, 0.37 g of ZnSO4, 0.37 g of CuSO4, and 2.98 g of ascorbic acid. After ball milling and mixing, sinter in nitrogen at 350 °C for 16 h, and then crush to obtain Na 2.5 Fe 1.73 Cu 0.01 Zn 0.01 (SO4)3@C. After testing, it is found that the carbon content in Na 2.5 Fe 1.73 Cu 0.01 Zn 0.01 (SO4)3@C is about 3.4%.

[0107] Comparative Example 2:

[0108] This comparative example provides a modified sodium sulfate, sodium iron sulfate cathode material and its preparation method.

[0109] (1) Modified sodium sulfate material NaSO4@C / N

[0110] Dissolve 893.3 g of sodium sulfate, 106.7 g of citric acid, and 10.67 g of PVP (K value is 18) in 10 L of pure water. After stirring evenly, obtain the precursor through spray drying. When spray drying, the inlet temperature is 180 °C, the outlet temperature is 80 °C, the feeding rate is 2000 ml / h, and the atomizer frequency is 300 Hz. Sinter the precursor in a nitrogen atmosphere at 650 °C for 10 h to obtain nitrogen-doped carbon-coated sodium sulfate, namely NaSO4@C / N, Figure 4 which is the SEM image thereof.

[0111] (2) Sodium iron sulfate Na 2.5 Fe 1.73 Cu 0.01 Zn0.01 (Preparation of (SO4)3@C / N)

[0112] According to Na 2.5 Fe 1.73 Cu 0.01 Zn 0.01 (SO4)3, take 40.04 g of NaSO4@C / N, 60.17 g of FeSO4, 0.37 g of ZnSO4, 0.37 g of CuSO4, and 2.98 g of ascorbic acid. After ball milling and mixing, sinter at 350 °C in nitrogen for 16 h, and then pulverize to obtain Na 2.5 Fe 1.73 Cu 0.01 Zn 0.01 (SO4)3@C / N. After testing, it is found that the carbon content in Na 2.5 Fe 1.73 Cu 0.01 Zn 0.01 (SO4)3@C / N is about 3.68%.

[0113] Comparative Example 3

[0114] This comparative example provides a modified sodium sulfate, sodium iron sulfate cathode material and its preparation method.

[0115] (1) Preparation of modified sodium sulfate material NaSO4@C / N

[0116] Dissolve 786.4 g of sodium sulfate, 213.6 g of citric acid, and 12.82 g of glycine in 10 L of pure water. After stirring evenly, obtain the precursor by spray drying. When spray drying, the inlet temperature is 210 °C, the outlet temperature is 100 °C, the feeding rate is 2000 ml / h, and the atomizer frequency is 300 Hz. Sinter the precursor in a nitrogen atmosphere at 750 °C for 8 h to obtain carbon-coated sodium sulfate, namely NaSO4@C / N.

[0117] (2) Preparation of sodium iron sulfate Na 2.5 Fe 1.72 Cu 0.01 Ni 0.01 Zn 0.01 (SO4)3@C / N

[0118] According to Na 2.5 Fe 1.72 Cu 0.01 Ni 0.01 Zn 0.01(SO4)3 has a molar ratio of 40.04 g of NaSO4@C, 59.60 g of FeSO4, 0.35 g of NiSO4, 0.37 g of ZnSO4, 0.37 g of CuSO4, and 2.98 g of ascorbic acid. After ball milling and mixing, it is sintered at 380 °C in nitrogen for 12 h, and then pulverized to obtain Na 2.5 Fe 1.72 Cu 0.01 Ni 0.01 Zn 0.01 (SO4)3@C / N. After testing, it is found that the carbon content in Na 2.5 Fe 1.72 Cu 0.01 Ni 0.01 Zn 0.01 (SO4)3@C / N is approximately 6.9%.

[0119] Comparative Example 4

[0120] This comparative example provides a modified sodium sulfate, sodium iron sulfate cathode material and its preparation method.

[0121] (1) Preparation of modified sodium sulfate material NaSO4@C / N

[0122] Dissolve 900 g of sodium sulfate, 100 g of glucose, and 10 g of PVP (K value is 30) in 10 L of pure water. After stirring evenly, obtain the precursor by spray drying. When spray drying, the inlet temperature is 160 °C, the outlet temperature is 80 °C, the feed rate is 2000 ml / h, and the atomizer frequency is 300 Hz. Sinter the precursor in a nitrogen atmosphere at 550 °C for 10 h to obtain nitrogen-doped carbon-coated sodium sulfate, that is, NaSO4@C / N.

[0123] (2) Preparation of sodium iron sulfate Na 2.5 Fe 1.75 (SO4)3@C / N

[0124] According to the molar ratio of Na 2.5 Fe 1.75 (SO4)3, take 40.45 g of NaSO4@C / N, 60.56 g of FeSO4, and 3.03 g of ascorbic acid. After ball milling and mixing, sinter at 350 °C in nitrogen for 16 h, and then pulverize to obtain Na 2.5 Fe 1.75 (SO4)3@C / N. After testing, it is found that the carbon content in Na 2.5 Fe 1.75 (SO4)3@C / N is approximately 3.53%.

[0125] Performance test:

[0126] (1) Expose the cathode materials prepared in the above examples and comparative examples to air at 25°C and a humidity of 70%, and take samples at different times to measure their moisture change values (unit: ppm). The results are shown in Table 1 below:

[0127] Table 1

[0128] Initial 1 day 3 days 7 days Example 1 560 1060 2030 3140 Example 2 643 890 1567 2990 Example 3 558 1068 2649 3080 Example 4 686 1152 2390 3568 Example 5 557 1139 2058 3320 Comparative Example 1 1450 4279 8360 12147 Comparative Example 2 1240 3032 6820 8580 Comparative Example 3 1060 2750 6799 7980 Comparative Example 4 898 2450 7290 8950

[0129] As can be seen from Table 1, for the sodium iron sulfate cathode material in the examples of the present invention, its initial moisture content is all below 900 ppm and the increasing trend of its moisture content is significantly lower than that of each comparative example.

[0130] (2) Use the cathode materials prepared in the above examples and comparative examples as the cathode active material and sodium flakes as the anode for the preparation of sodium-ion batteries. The specific steps are as follows: Mix the cathode active material, conductive carbon black, and polyvinylidene fluoride in a mass ratio of 90:5:5 evenly, and then mix it evenly with the N-methylpyrrolidone solvent. Coat the mixed slurry on the aluminum foil and dry it in vacuum at 110°C for 12 h. Cut it into circular pieces with a diameter of 12 mm for standby to obtain the cathode electrode sheets. Use metallic sodium as the counter electrode, glass fiber as the separator, and 1 mol / L sodium hexafluorophosphate (NaPF6) ethylene methyl carbonate (EMC) solution as the electrolyte, and assemble it into a button cell in a glove box under an Ar atmosphere with a water partial pressure less than 0.1 ppm and an oxygen partial pressure less than 0.1 ppm. Use a Blue Power battery test system, the voltage range for cyclic testing is 2.5 - 4.3 V, and the voltage range for other electrochemical tests is 2 - 4.5 V, 1C = 110 mAh / g. The test methods are as follows, and the test results are shown in Table 2 and Figure 5 、 6 as shown, where Figure 5 is the charge-discharge curve of Example 1 and Comparative Example 2 at 0.1C, Figure 6 is the 5C cyclic curve of Example 1 and Comparative Example 1, Comparative Example 2.

[0131] Discharge specific capacity test: After the battery is assembled, let it stand for 12 h, then charge it to 4.5 V at 0.1C, and then continue to charge at a constant voltage of 4.5 V until the current is less than 0.05C to stop charging. After standing for 2 min, discharge it at 0.1C until the voltage is less than 2V to end the discharge, and obtain the first-cycle charge-discharge capacity at 0.1C. After standing for 2 min, charge it to 4.5 V at 1C, and then continue to charge at a constant voltage of 4.5 V until the current is less than 0.05C to stop charging. After standing for 2 min, discharge it at 1C until the voltage is less than 2V to end the discharge, and obtain the charge-discharge capacity at 1C. After standing for 2 min, charge it to 4.5 V at 5C, and then continue to charge at a constant voltage of 4.5 V until the current is less than 0.05C to stop charging. After standing for 2 min, discharge it at 5C until the voltage is less than 2V to end the discharge, and obtain the charge-discharge capacity at 5C.

[0132] Capacity retention rate: ① After the battery is assembled, it is left standing for 12 h, then charged at 0.1 C to 4.3 V, followed by constant voltage charging at 4.5 V until the current is less than 0.05 C, then the charging is stopped. After standing for 2 min, it is discharged at 0.1 C until the voltage is less than 2.5 V, and the discharging ends; ② After standing for 2 min, step ① is repeated at 0.2 C / 0.5 C / 1 C respectively; ③ Then step ① is repeated at 5 C to obtain the first-cycle discharge capacity at 5 C. Finally, it is cycled 500 times at 5 C, and the capacity retention rate is calculated based on the first-cycle discharge capacity at 5 C.

[0133] Table 2

[0134]

[0135]

[0136] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those of ordinary skill in the art should understand that they can still modify the technical solutions described in the foregoing embodiments, or perform equivalent replacements on some or all of the technical features; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A modified sodium sulfate material, characterized in that, It includes a housing and prismatic particles located within the housing. The composition of the housing includes N and C, and the composition of the prismatic particles includes C and sodium sulfate.

2. The modified sodium sulfate material according to claim 1, wherein The prismatic particles are aggregated by rod-shaped particles; and / or The moisture content of the modified sodium sulfate material is ≤1000 ppm.

3. The modified sodium sulfate material according to claim 1 or 2, characterized in that, The diameter of the rod-shaped particles is 200 - 600 nm, and the length is 7 - 12 μm; and / or The diameter of the housing is 15 - 25 μm.

4. A method for preparing the modified sodium sulfate material according to any one of claims 1-3, characterized in that, It at least includes the steps of preparing a precursor by spray-drying a precursor material containing a carbon source, a nitrogen source, and sodium sulfate, and sintering the precursor under a protective atmosphere to obtain the modified sodium sulfate. Among them, the viscosity of the nitrogen source is higher than that of the carbon source, the carbon source is an organic carbon source, the K value of the nitrogen source ≥23, and the dosage of the nitrogen source is 5 - 10 wt% of the carbon source.

5. The preparation method according to claim 4, characterized in that, The inlet temperature of spray-drying is 160 - 210 °C, the outlet temperature is 60 - 100 °C, the sintering temperature of the precursor is 500 - 800 °C, and the sintering time is 6 - 12 h; and / or The carbon source is one or more of citric acid, glucose, folic acid, fructose, lactose, sucrose, maltose, starch, and the nitrogen source is PVP.

6. A sodium iron sulfate cathode material, characterized in that, The structural general formula of the sodium iron sulfate cathode material is Na 2.5 Fe 1.75-x A x (SO4)3@CN, where 0 < x ≤ 0.05 and the A ion is a hydrophobic metal ion.

7. The sodium iron sulfate cathode material according to claim 6, characterized in that, After doping metal ions into the sodium iron sulfate cathode material, the diffraction peak of the crystal plane at 15.45° in its X-ray diffraction pattern shifts to the left, and the shift amplitude is 0 - 0.2°; and / or The moisture content of the sodium iron sulfate cathode material is ≤900 ppm.

8. The sodium iron sulfate cathode material according to claim 6 or 7, characterized in that, The A ion and Fe 2+ have different ionic radii; and / or The A ion is Mg 2+ , Ni 2+ , Cu 2+ , Zn 2+ or one or more of them.

9. The sodium iron sulfate cathode material according to any one of claims 6-8, characterized in that, The sodium iron sulfate cathode material is prepared from a mixed material including the modified sodium sulfate material according to any one of claims 1 - 3 or the modified sodium sulfate material prepared by the preparation method according to claim 4 or 5, an iron source, and a doping metal A with a mass ratio ≥0.

10. The sodium iron sulfate cathode material according to claim 9, wherein, The mixed material is sintered under a protective atmosphere to obtain the sodium iron sulfate cathode material. The sintering temperature of the mixed material is 320 - 400 °C, and the sintering time is 8 - 24 h; and / or The mixed material is ball-milled and then sintered; among them, the ball-milling speed is 200 - 500 r, and the time is 1 - 5 h; and / or The mixed material also includes a reducing agent, and the reducing agent is selected from one or more of ascorbic acid, oxalic acid, citric acid, pyrrole, tea polyphenols, or sodium sulfite.

11. A cathode material, characterized in that, It includes the sodium iron sulfate cathode material according to any one of claims 6 - 10.

12. A positive electrode sheet, characterized in that, It includes the cathode material according to claim 11.

13. A sodium-ion battery, characterized in that, It includes the cathode plate according to claim 12.

14. An electronic device, characterized in that, It includes the sodium-ion battery according to claim 13.